Mental health literacy in Pakistan: a narrative review - Begum, Rubina; Choudhry, Riaz Fahad; Khan, Tahir Mehmood; Bakrin, Faizah Safina; Al-Worafi, Yaser Mohammed; Munawar, Khadeeja (Emerald Group Publishing Ltd., 2019)
Abstract Purpose – The term ‘‘Mental health literacy’’ is defined as knowledge and beliefs about mental disorders which aid their recognition, management or prevention. The importance of health literacy for physical health is widely studied; however, the area of mental health literacy in Pakistan has been comparatively neglected. The purpose of this paper is to address the knowledge about mental health in people living in Pakistan. Design/methodology/approach – Relevant literature relating to mental health literacy was identified through various database searches. The databases searched included: PubMed, Cochrane database of Systemic Reviews, PsycINFO using the terms mental health, mental health literacy, mental health education, Pakistan. Findings – Literature suggests that there is dearth of knowledge about mental illnesses and their treatment among public. This review also highlights the importance of mental health literacy among professionals working in the field of health care. In Pakistan, due to low literacy rate, a high percentage of poverty and dearth of trained professionals warrants an emendation in approaches established for attaining the goal of public health and psychiatric care. Practical implications – Findings have implications for practitioners in the field of mental health care as well as designing targeted interventions for enhancing mental health literacy and help-seeking behavior in the future. Originality/value – A limited understanding and lack of improvement in mental health literacy may interfere with society’s acceptance of evidence-based mental health care which may hamper the delivery of adequate mental health services to the needy